PENAMPILAN BIBIT DAN TANAMAN BELUM MENGHASILKAN DELAPAN KOMBINASI PERSILANGAN SAWIT [THE APPEARANCE OF SEEDLINGS AND IMMATURE PLANTS EIGHT COMBINATIONS OF OIL PALM CROSSES] - Budi Santosa; Yulianus R. Matana; Ismail Maskromo; Donata S. Pandin; Steivie Karouw (Pusat Penelitian dan Pengembangan Perkebunan, 2021)
Oil palms in the nursery phase and young oil palms in the Immature Plant (TBM) phaseare one of the important stages to consider so that the plants can grow well. The purpose of this study was to determine oil palm plantations in the nursery phase and oil palm young plants in the Immature Plant phase 8 combination accessions of oil palms. The research was conducted at the Sitiung Experimental Garden, Dharmasraya Regency, West Sumatra from 2017 - 2019 using the Single Block method and Complete Randomized Block Design (CRBD). The characters observed included: plant height, number of leaves, length of petiole, length of rachis, length of leaves, speed of leaf breaking.The data obtained were analyzed using the SAS program and its genetic diversity. In the nursery phase until the age of 12 months, 8 combination accessions of oil palms were based on statistical analysis and there was no significant difference for the character of plant height and number of leaves. The plant height has moderate genetic diversity, and the plant height increases around 4.95 - 6.50 cm per month. Oil palm accession D2.3 x P 108 (88.80 cm) was the highest combination accession of crossed palms with the highest plant height increase of 6.5 cm per month. The number of leaves ranged from 10.30 - 13.00 leaves with low to moderate genetic diversity. Accession T23.3 x P109 had the highest number of leaves, namely 13.00 leaves with an increase in the number of leaves of 0.81 leaves per month. The eight combined accessions of crossed palms began to break leaves at about 7 months of age.In the Immature Plant (IP) phase, based on the results of statistical analysis for the observed characters, the results were no significant difference. Oil palm plants in the TBM 1 phase have the characters of plant height more than 222 cm, number of leaves more than 15 leaves, and petiol length of more than 33 cm with generally moderate genetic diversity, except for the length of the petiole for oil palm accession T 23.8 x P108, D2.3 x P108 and P108 T23.2 x has a fairly high genetic diversity. Oil palm accession T23.8 x P108 had the highest plant height (241.17 cm), while oil palm accession D91.8 x DL7 / 1 had the highest number of leaves, namely 18.44 leaves, and palm accession T23.2 x P108 has the longest case of 37.72 cm. Oil palm plants in the IP 2 phase have the characters of the number of leaflets, petiol lengths, rachis lengths, and leaf lengths between the combination of palm crossings which have low diversity. The spiny leaf midrib and the position of the leaflets alternate, the number of leaflets between the left and right sides is not the same.Accession D43.7 x P109 has a number of leaflets at most about 86 leaflets. Palm accession T23.3 x P109 has the longest characters for the length of the petiol, the length of the rachis, and the length of the leaves. The fastest combination accession of crossed palms produced the first flowers, namely T23.8 x P108, T23.3 x P109, and T23.3 x P108.Abstrak Tanaman sawit pada fase pembibitan dan tanaman muda sawit pada fase Tanaman Belum Menghasilkan (TBM) merupakan salah satu tahap yang penting untuk diperhatikan agar tanaman dapat tumbuh dengan baik. Tujuan dari penelitian ini adalah untuk mengetahui tanaman sawit pada fase pembibit dan tanaman muda sawit pada fase Tanaman Belum Menghasilkan 8 aksesi kombinasi persilangan sawit. Penelitian dilaksanakan di Kebun Percobaan Sitiung, Kabupaten Dharmasraya, Sumatera Barat sejak tahun 2017 – 2019 dengan menggunakan metode Blok Tunggal dan Rancangan Acak Kelompok Lengkap (RAKL). Karakter yang diamati antara lain: tinggi tanaman, jumlah daun, panjang petiol, panjang rachis, panjang daun, kecepatan pecah daun. Data yang diperoleh dianalisa dengan menggunakan program SAS dan keragaman genetiknya. Pada fase pembibitan sampai umur 12 bulan, 8 aksesi kombinasi persilangan sawit berdasarkan analisis statistik tidak ada beda nyata untuk karakter tinggi tanaman dan jumlah daun. Tinggi tanaman memiliki keragaman genetik termasuk sedang, dan pertambahan tinggi tanaman sekitar 4,95 – 6,50 cm per bulan. Aksesi sawit D2.3 x P 108 (88,80 cm) merupakan aksesi kombinasi persilangan sawit paling tinggi dengan pertambahan tinggi tanaman paling tinggi 6,5 cm per bulan. Jumlah daun berkisar 10,30 – 13,00 daun dengan keragaman genetik rendah sampai sedang. Aksesi T23.3 x P109 memiliki jumlah daun paling banyak yaitu 13,00 daun dengan pertambahan jumlah daun 0,81 daun per bulan. Delapan aksesi kombinasi persilangan sawit mulai pecah daun pada umur sekitar 7 bulan. Pada fase Tanaman Belum Menghasilkan (TBM), berdasarkan hasil analisis statistik untuk karakter yang diamati hasilnya tidak ada beda nyata. Tanaman sawit pada fase TBM 1 memiliki karakter tinggi tanaman lebih dari 222 cm, jumlah daun lebih dari 15 daun, dan panjang petiol lebih dari 33 cm dengan keragaman genetik pada umumnya termasuk sedang, kecuali karakter panjang petiol untuk aksesi sawit T 23.8 x P108, D2.3 x P108, dan T23.2 x P108 memiliki keragaman genetik cukup tinggi. Aksesi sawit T23.8 x P108 memiliki tinggi tanaman paling tinggi (241,17 cm), sedangkan aksesi sawit D91.8 x DL7/1 memiliki jumlah daun paling banyak yaitu 18,44 daun, dan aksesi sawit T23.2 x P108 memiliki petiol paling panjang 37,72 cm. Tanaman sawit pada fase TBM 2 mempunyai karakter jumlah anak daun, panjang petiol, panjang rachis, dan panjang daun antar kombinasi persilangan sawit memiliki keragaman rendah. Pelepah daun berduri dan posisi anak daun selang-seling, jumlah anak daun antara sebelah kiri dan kanan tidak sama. Aksesi D43.7 x P109 memiliki jumlah anak daun paling banyak sekitar 86 anak daun. Aksesi sawit T23.3 x P109 memiliki karakter paling panjang untuk panjang petiol, panjang rachis, dan panjang daun. Aksesi kombinasi persilangan sawit paling cepat keluar bunga pertama yaitu T23.8 x P 108, T23.3 x P109, dan T23.3 x P 108.